Pengaruh model pembelajaran inquiry based learning terhadap kemampuan berfikir kritis Siswa pada Mata Pelajaran PPKn Kelas X SMA Negeri 8 Muaro Jambi - Halimah, Halimah; Anderson, Irzal; Usmanto, Heri (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aims of this writing is to identificate the influence of the Inquiry Based Learning Model on Students' Critical Thinking Ability in Class X Civics Subjects at SMA Negeri 8 Muaro Jambi odd semester of the 2023/2024 academic year. This writing implemented a quantitative approach with a quasi-experiment design, a Pretest-Posttest Control Group Design research design. Class X SMA Negeri 8 Muaro Jambi was the population used, it was made up of 2 classes, namely class X E2 as the experimental class and class Meanwhile, data was acquired from tests in the form of questions given to students. After obtaining answers from the test, quantitative analysis is then carried out. The data analysis method used is the experimental class and control class t-test in order to ascertain how the IBL learning model affects students' critical thinking abilities. According to the data analysis derived from the output of independent sample t-test that used in hypothesis testing, the tcount>ttable value was obtained, the ttable value was 1,669. then tcount > ttable, namely 9.386 > 1.669 and a sig (2-tailed) value of 0.000 > 0.005 is obtained, it show that the IBL learning model impacts students critical thinking abilities in Class X Civics subjects at SMA Negeri 8 Muaro Jambi in the odd semester of the 2023/2024 academic year.